Sejarah dan Pelestarian Genderang Sisibah sebagai Warisan Budaya Suku Pakpak di Kabupaten Dairi - Sonia Fadilah; Fauziah Lubis; Khoirul Jamil (Local History & Heritage, 2021)
This study aims to determine the history of the Sisibah Drum, the preservation and use and function of the Sisibah Drum. The benefits of this research can add insight or expand the knowledge of writers and readers about the History and Preservation of the Sisibah Drum and make useful information materials for the government and the community, especially the Pakpak Dairi community. This study uses an anthropological approach, because it examines cultural preservation in historical studies. Historical methods such as collecting data sources, verification, interpretation and historical are used in this research in the form of qualitative research. This musical instrument was used before Islam came to Pakpak Dairi's land. The Sisibah drum is one of the cultural heritages of the previous Pakpak ancestors. The Sisibah drum is a musical instrument that has characteristics with different shapes and different rhythmic tones.